Interindividual Variation in Metabolism of Soy Isoflavones and Lignans: Influence of Habitual Diet on Equol Production by the Gut Microflora - Rowland, Ian R.; Wiseman, Helen; Sanders, Tom A. B.; Adlercreutz, Herman; Bowey, Elizabeth A. (Nutrition and cancer, 2000)
The soy isoflavones, daidzein and genistein, and the lignans, matairesinol and secoisolariciresinol, are phytoestrogens metabolized extensively by the intestinal microflora. Considerable important evidence is already available that shows extensive interindividual variation in isoflavone metabolism, and we have investigated the extent of this variation in a crossover study of a soy-containing food low or high in isoflavones (each treatment period lasted for 17 days, and the 2 treatment periods were separated by a 25-day washout period) in 24 healthy subjects [19 women and 5 men, mean age 30 yr, range 19-40, mean body mass index 22.5 ±3.5 (SD) kg/m2]. There was a 16-fold variation in total isoflavonoid excretion in urine after the high-isoflavone treatment period. The variation in urinary equol excretion was greatest (664-fold), and subjects fell into two groups: poor equol excretors and good equol excretors (36%). A significant negative correlation was found between the proportion of energy from fat in the habitual diet and urinary equol excretion (r = -0.55; p = 0.012). Good equol excretors consumed less fat as percentage of energy than poor excretors (26 ± 2.3% compared with 35 ± 1.6%, p < 0.01) and more carbohydrate as percentage of energy than poor excretors (55 ± 2.9% compared with 47 ± 1.7%, p < 0.05). Interindividual variation in the urinary excretion of O-desmethylangolensin (O-DMA) was also apparent (76-fold after the high-isoflavone treatment period), but there was no relationship between equol excretion and O-DMA excretion. Enterolactone was the major lignan metabolite in urine and plasma but showed less interindividual variation than equol and O-DMA. It is suggested that the dietary fat intake decreases the capacity of gut microbial flora to synthesize equol.